2005
DOI: 10.1002/jcp.20473
|View full text |Cite
|
Sign up to set email alerts
|

LIGHTing up dendritic cell activation: Immune regulation and viral exploitation

Abstract: The maturation state of dendritic cells (DC) is regulated by a variety of factors. These include ligands expressed by T cells, such as members of the TNF superfamily. Recent studies have highlighted the role of one such molecule, LIGHT, as a positive regulator of DC biology, promoting the maturation of these cells through the activation of NF-kB pathways. In addition, HSV-1 envelope glycoproteins can also bind the LIGHT receptor, herpes virus entry mediator (HVEM), and activate similar downstream signalling pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…One of the known receptors for gD is HVEM (54, 55), a TNF receptor family member that is known to signal via NF-B in response to its natural ligand LIGHT (32)(33)(34)56). Signaling via this receptor might therefore be an essential, although clearly not a sufficient event for DC maturation in our model.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the known receptors for gD is HVEM (54, 55), a TNF receptor family member that is known to signal via NF-B in response to its natural ligand LIGHT (32)(33)(34)56). Signaling via this receptor might therefore be an essential, although clearly not a sufficient event for DC maturation in our model.…”
Section: Discussionmentioning
confidence: 98%
“…The gD receptor HVEM is a member of the TNF receptor family and is known to transduce activation signals in response to its ligand LIGHT (32)(33)(34). Although gD alone failed to induce DC maturation, it remained possible that gD/HVEM interaction was one essential component in the overall activation process.…”
Section: The DC Response To Hsv-1 Glycoproteins Does Not Require Herpmentioning
confidence: 99%
“…No anti-host CTL activity was generated in the mice injected with HVEM-KO cells, in striking contrast to the ample CTL activity induced by a transfer of control lymphocytes ( Figure 4A). Considering the expression and function of HVEM on broad immune populations, including DC, T, and B cells, 32,33 we further dissected the functional role of HVEM on donor T and non-T cells using experiments similar to those described in Figure 1B. Anti-host CTL activity was completely abrogated when HVEM-KO T cells were transferred as donor cells, irrespective of the genotypes of cotransferred non-T cells, whereas a lack of HVEM on non-T cells did not hamper CTL generation when cotransferred with WT T cells ( Figure 4B).…”
Section: Essential Role Of Hvem On Donor T Cells In Their Survivalmentioning
confidence: 99%
“…As DCs play a central role in both the innate and adaptive immune systems, they represent a potential target for different pathogens to evade host immune responses [Jenne et al, 2001;Steinman and Nussenzweig, 2002;Pollara et al, 2005]. Several groups have demonstrated that the functionality of DCs is altered during the course of viral infections.…”
Section: Discussionmentioning
confidence: 99%